Challenges and opportunities for the development of MEGACITIES - Deren Li; Jun Ma; Tao Cheng; J. L. van Genderen; Zhenfeng Shao (International Journal of Digital Earth, 2019)
Urbanization is one of the most important social and economic phenomena in the world today. This paper reviews the formation of megacities and summarizes the main problems, challenges and opportunities faced by the sustainable development of such large megacities. Issues discussed include the problems of land subsidence in megacities, environmental issues, traffic problems and energy supply aspects. The sustainable development of megacities in other parts of the world provided the references and experiences for the countermeasures of megacity planning and development in China. The vision of Digital Earth and Digital Cities can play a major role in the efficient management and sustainable growth of such megacities all around the world.